Kontribusi Televisi Lokal TVku Semarang Dalam Membentuk Kompetensi Profesional Mahasiswa Melalui Program Magang Inkubator Kerja - Pamungkas, Hery; Hapsari, Retnaningtyas Niken; Umami, Zahrotul (Universitas Mercu Buana, 2022)
Based on Kemenristekdikti Press Release Number: 3 / SP / HM / BKKP / I / 2019 with “Research, Technology and Open Higher Education, Flexible and Excellent” themes, there are points that nowdays we need to prepare graduates who have competencies and work ability and employability by giving certification, increasing student achievement, and giving professional experience. TVKU as a local television in Semarang has an internship program called Incubator. This research aims to determine the extent of the relevance aspects of Incubator program towards formation of competencies and professional experience for students of Dian Nuswantoro University Semarang before they graduate from college and go into the real world of work. The method used in this research is descriptive. The data in this research were obtained by field studies through interviews, observation and documentation. The process of data analysis uses descriptive-qualitative analysis methods with the stages of data collection, data reduction, data presentation, decision making or verification. The results of this study, there is a relationship or relevance between TVKU Incubator programs with the formation of competencies and professional experience of students, proven by the existence of alumni who succeeded to work after joining the Incubator program.